Implementasi Program Percepatan Pembangunan Wilayah Lingkar Luar Kota Medan - Muhammad Ardian; Arief Marizki Purba (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This research aims to analyze the implementation of the Medan Outer Ring Acceleration Area Program in the Medan Tuntungan District and to find out the supporting and inhibiting factors. The research method used is descriptive research method with a qualitative approach. The results showed that the implementation of the accelerated development program for the outer ring region in Medan Tuntungan District was effective and was able to add and improve several facilities and infrastructures, not only road infrastructure, health infrastructure, educational infrastructure, but also added economic infrastructure. Factors that support infrastructure development in the District of Medan Tuntungan include Support of all citizens to government policies through proposals submitted to the Medan City Government regarding the need for infrastructure development in the District of Medan Tuntungan, in the context of accelerating regional development. Factors hampering infrastructure development in Medan Tuntungan Subdistrict are the lack of public awareness of the use and maintenance of infrastructure provided by the government, so that conditions are easily damaged and the limited regional budget for infrastructure development.